I’TIBĀR AL MA'ALAT PRINCIPLES IN MUI FATWA NUMBER 14 OF 2020 CONCERNING ORGANIZATIONS OF WORSHIP IN SITUATIONS OF THE COVID-19 OUTBREAK - Islamul Haq; Abdul Syatar; M. Ali Rusdi Bedong; Muhammad Haramain (Al-Risalah, 2021)
This study aims at examining the use the principle of i`tibar al ma'alat in the MUI fatwa number 14 of 2020 concerning the organization of worship in situations of the Covid-19 outbreak. MUI fatwa number 14 of 2020 forced most Muslims in Indonesia to worship out of the box. the results of the study it was found that the MUI in issuing fatwa number 14 of 2020 had considered the principle of i'tibar al ma'alat, the prohibition of worshiping in congregation in areas with high distribution potential was determined in order to anticipate the spread of the Covid-19 outbreak. However, the MUI does not generalize all regions, this is also done based on the principle of i'tibar al ma'alat to avoid the practice of tafrith to religious orders in the midst of society